Bafilomycins N and O, novel cytotoxic bafilomycin analogues produced by Streptomyces sp. GIC10-1 isolated from marine sponge Theonella sp. Issue 34 (24th August 2017) - Chen, Yu-Hsin; Yang, Juan-Cheng; Lu, Mei-Chin; Weng, Ching-Feng; Su, Yin-Di; Kuo, Jimmy; Wu, Yang-Chang; Sung, Ping-Jyun
Abstract: Two novel 16-membered tetraene marcolides, bafilomycins N (1 ) and O (2 ), along with two known analogues, JBIR-100 (3 ) and bafilomycin K (4 ) were produced from isolate GIC10-1, a Streptomyces sp. strain that was originally cloned from bacterial communities associated with marine sponge Theonella sp. The structures of new bafilomycins1 and2 were established by using spectroscopic methods and comparing the spectroscopic data with those of known related metabolites. Compounds1 and2 were proven to be the first 14-methylbafilomycins to be isolated. Cytotoxicity of these compounds toward various cancer cell lines also is described. Graphical abstract: